A Study on Mesoporous Silica Loaded With Novel Photosensitizers HCE6 and Oxaliplatin for the Treatment of Cholangiocarcinoma - Zhang, Pei-Jian; Liu, Meng-Dong; Fan, Fang-Yong; Liu, Ke-Xia (Frontiers in Oncology, 2021)
Purpose: Cholangiocarcinoma (CCA) is a malignant tumor with a high incidence. The therapeutic effect of conventional chemotherapy and radiotherapy is not obvious. Photodynamic therapy (PDT) is an ideal modality to fight cancer, and the nature of photosensitizer limits its application in clinical therapy. The aim of this study was to explore a novel mode of drug delivery for the intervention of bile duct cancer. Methods: Oxaliplatin and photosensitizer HCE6 were loaded with mesoporous silica nanoparticles (MSNs) to synthesize Oxaliplatin/HCE6-MSNs (OH-MSNs); the structure of OH-MSNs was characterized by transmission electron microscopy (TEM) and dynamic light scattering (DLS), the drug release rate was detected by high performance liquid chromatography; the cellular activity, apoptosis level, and the expression levels of intracellular apoptosis and autophagy-related factors of OH-MSNs on cholangiocarcinoma cells were observed by CCK-8, flow cytometry, colony formation assay, and Western blot; the effects of OH-MSNs on cholangioma growth were observed by mouse tumor formation, immunohistochemistry, and tissue Tunel staining. Results: The release of OH-MSNs to Oxaliplatin was enhanced under acidic conditions; compared with Oxaliplatin or O-MSNs, OH-MSNs showed more potent killing effects against cholangiocarcinoma cells (P<0.05), and exerted notably inhibitory effects on the activity of cholangiocarcinoma cells (P<0.05), promoted their apoptosis (P<0.05), and greatly facilitated the expression of pro-apoptotic factors and autophagic factors in cholangiocarcinoma cells (P<0.05), and markedly inhibited the expression of anti-apoptotic factors and autophagic inhibitory factors (P<0.05); moreover, OH-MSNs could significantly suppress the growth of mouse cholangiocarcinoma (P<0.05) and induce apoptosis of tumor cells compared with Oxaliplatin or O-MSNs (P<0.05). Conclusion: MSNs loading greatly increases the killing effect of Oxaliplatin on cholangiocarcinoma cells and upgrades the autophagic level of cholangiocarcinoma cells, while OH-MSNs synthesized by further loading HCE6 have a more apparent killing effect on cholangiocarcinoma cells.